An Overview on Genistein and its Various Formulations - Jaiswal, Neha; Akhtar, Juber; Singh, Satya Prakash; Badruddeen; Ahsan, Farogh (Drug Research, 2019)
Genistein is the natural isoflavone and a phytoestrogen with a broad range of pharmacological properties, such as tyrosine and topoisomerase inhibition. It also induces apoptosis and cell proliferation inhibition, differentiates cancer cells. Added health benefits include the reduction of osteoporosis by suppressing osteoclasts and lymphocyte functions, decreased the risk of cardiovascular attacks and relieved postmenopausal problems. Genistein traditionally used in Chinese and Ayurvedic medicine and are found to be associated with lower risk of breast, prostate and lung cancer. Numerous factors comprising genetic, epigenetic and transcriptomic alterations are evidenced to be responsible for breast, prostate and lung cancer. In present review, an overview on genistein, the various analytical methods and drug delivery approaches to determine genistein in the formulations are discussed. It may help to develop novel formulations with better solubility and bioavailability of genistein. The tumor cell scan may be targeted to form a stable genistein formulation.
Keywords: apoptosis; breast cancer; genistein; nanoformulations